The Effectiveness of Law Enforcement Against Trademark Infringement in Online Commerce in Indonesia - Gia Anggiani; Hani Sri Handayani; Dila Nurul Maghfira Arrahman; Neng Yani Nurhayani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effectiveness of law enforcement against trademark infringement in online commerce in Indonesia through a normative juridical research approach. The analysis is based on statutory regulations, international intellectual property instruments, policy documents, and scholarly literature concerning trademark protection, electronic commerce, and digital governance. The findings indicate that Indonesia possesses a relatively comprehensive legal framework for trademark protection, supported by national legislation and international intellectual property standards. Nevertheless, the practical effectiveness of enforcement remains limited due to institutional coordination problems, difficulties in identifying online offenders, challenges associated with digital evidence, marketplace supervision limitations, and procedural barriers affecting criminal and civil remedies. The study identifies a persistent gap between normative legal objectives and enforcement realities within digital commercial environments. To address these challenges, the research proposes an integrated reform model emphasizing regulatory innovation, marketplace accountability, artificial intelligence based monitoring systems, alternative dispute resolution mechanisms, preventive legal protection, and enhanced stakeholder cooperation. The study argues that effective trademark protection in digital commerce requires the convergence of legal certainty, technological capability, and adaptive governance structures capable of responding to evolving patterns of online infringement.